Expression and Diagnostic Value of Nrf2 and p62 in Cervical Squamous Cell Carcinoma and Intraepithelial Lesions - Wei W; Hu X; Han Q (Cancer Management and Research, 2025)
Wei Wei, Xingyan Hu, Qing Han Department of Gynaecology, Yichang Central People’s Hospital, The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, People’s Republic of ChinaCorrespondence: Qing Han, Department of Gynaecology, Yichang Central People’s Hospital, The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, People’s Republic of China, Email maria_hanqing@163.comBackground: This study aims to explore the value of Nuclear Transcription Factor Erythroid 2-Related Factor 2 (Nrf2) and the selective autophagy adapter protein p62/Sequestosome 1 (SQSTM1) in diagnosing cervical squamous cell carcinoma (SCC) and squamous intraepithelial lesions (SIL).Methods: Paraffin specimens from 125 cervical SCC patients, 102 low-grade SIL (LSIL) patients, 101 high-grade SIL (HSIL) patients, and 49 patients with benign/reactive cervical squamous epithelium were collected at Yichang Central People’s Hospital from 2010 to 2023. Immunohistochemistry was used to detect Nrf2 and p62 expression. Positive expression was defined by visible light yellow, brownish-yellow, or brown cytoplasmic particles. The correlation between the two proteins and their diagnostic value were analyzed.Results: Both Nrf2 and p62 were predominantly localized to the cytoplasm in various cervical lesions. The expression levels of Nrf2 and p62 were significantly higher in LSIL, HSIL, and SCC than in benign/reactive epithelium (all P< 0.001), and lower in LSIL than in HSIL and SCC (all P< 0.001). A positive correlation was found between Nrf2 and p62 in all lesion types (all P< 0.05). ROC analysis indicated that the diagnostic accuracy was enhanced when Nrf2 and p62 were used in combination, as opposed to using either marker individually.Conclusion: Nrf2 and p62 are either not expressed or expressed at low levels in benign/reactive squamous epithelium, with expression increasing in LSIL, and being highest in HSIL and SCC. Both markers show a positive correlation across different cervical lesions, and either Nrf2 or p62 alone can effectively diagnose various cervical lesions, with even better diagnostic outcomes when used in combination.Keywords: nuclear factor erythroid 2-related factor 2, Nrf2, p62, cervical squamous cell carcinoma, SCC, intraepithelial lesions, diagnostic biomarkers